2021
DOI: 10.1177/02601060211032101
|View full text |Cite
|
Sign up to set email alerts
|

The association between binge eating disorder and weight management in overweight and obese adults: A systematic literature review

Abstract: Aim: Weight loss is shown to improve obesity-related health problems as long as it is maintained for a long term. The purpose of this systematic review was to investigate the association between binge eating disorder and weight management in overweight and obese adults. Methods: A systematic search following the preferred reporting items for systematic reviews and meta-analyses guidelines was conducted across PubMed, Ebsco and Cochrane Library from inception through December 2020 to identify studies that asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…On the other side, they also rated their diet and healthy eating habits slightly better than men, which is in accordance with other reports ( 42 ). Regrettably, we did not collect data about binge eating behaviour, which could have brought some insight into the mechanisms of weight cycling ( 43 ). A recent review has shown that women report higher levels of clinical and subclinical types of eating disorders, including binge eating and loss-of-control eating ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, they also rated their diet and healthy eating habits slightly better than men, which is in accordance with other reports ( 42 ). Regrettably, we did not collect data about binge eating behaviour, which could have brought some insight into the mechanisms of weight cycling ( 43 ). A recent review has shown that women report higher levels of clinical and subclinical types of eating disorders, including binge eating and loss-of-control eating ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the Body Mass Index-Standard Deviation Score (BMI-SDS) describes the individual deviations from the mean values for age and sex. As far as we could determine, the influence of eating disorders, i.e., binge-eating symptoms, has been studied exclusively in adults, with the evidence mostly supporting a negative influence on long-term weight loss success [ 15 , 16 , 17 ]. In previous studies, motivation produced mixed results as a predictor for weight loss success, often with only parents being surveyed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%